Bloom's Taxonomical Learning Theory And Educational Development In Indonesia - Friska Rahmatika Azizah (STIT Attaqwa, 2023)
In learning theory, Bloom's taxonomy is also one of the theories used in Indonesia because the theory is in accordance with the needs of educational development in Indonesia. Bloom's taxonomy is not only suitable for elementary and high school students, but also at kindergarten level because it can increase creativity. think critically, and independently.. Bloom's Taxonomy is centered on taxonomies created for educational purposes. This taxonomy was first compiled by Benjamin S. Bloom in 1956. In this case, educational goals are divided into several domains and each domain is subdivided into deeper divisions based on its hierarchy. Educational goals are divided into three realms or domains, namely: 1. Cognitive Domain, 2. Affective Domain, 3. Psychomotor Domain.